theory Height
imports "HOL-Nominal.Nominal"
begin
text \<open>
A small problem suggested by D. Wang. It shows how
the height of a lambda-terms behaves under substitution.
\<close>
atom_decl name
nominal_datatype lam =
Var "name"
| App "lam" "lam"
| Lam "\name\lam" ("Lam [_]._" [100,100] 100)
text \<open>Definition of the height-function on lambda-terms.\<close>
nominal_primrec
height :: "lam \ int"
where
"height (Var x) = 1"
| "height (App t1 t2) = (max (height t1) (height t2)) + 1"
| "height (Lam [a].t) = (height t) + 1"
apply(finite_guess add: perm_int_def)+
apply(rule TrueI)+
apply(simp add: fresh_int)
apply(fresh_guess add: perm_int_def)+
done
text \<open>Definition of capture-avoiding substitution.\<close>
nominal_primrec
subst :: "lam \ name \ lam \ lam" ("_[_::=_]" [100,100,100] 100)
where
"(Var x)[y::=t'] = (if x=y then t' else (Var x))"
| "(App t1 t2)[y::=t'] = App (t1[y::=t']) (t2[y::=t'])"
| "\x\y; x\t'\ \ (Lam [x].t)[y::=t'] = Lam [x].(t[y::=t'])"
apply(finite_guess)+
apply(rule TrueI)+
apply(simp add: abs_fresh)
apply(fresh_guess)+
done
text\<open>The next lemma is needed in the Var-case of the theorem below.\<close>
lemma height_ge_one:
shows "1 \ (height e)"
by (nominal_induct e rule: lam.strong_induct) (simp_all)
text \<open>
Unlike the proplem suggested by Wang, however, the
theorem is here formulated entirely by using functions.
\<close>
theorem height_subst:
shows "height (e[x::=e']) \ ((height e) - 1) + (height e')"
proof (nominal_induct e avoiding: x e' rule: lam.strong_induct)
case (Var y)
have "1 \ height e'" by (rule height_ge_one)
then show "height (Var y[x::=e']) \ height (Var y) - 1 + height e'" by simp
next
case (Lam y e1)
hence ih: "height (e1[x::=e']) \ ((height e1) - 1) + (height e')" by simp
moreover
have vc: "y\x" "y\e'" by fact+ (* usual variable convention *)
ultimately show "height ((Lam [y].e1)[x::=e']) \ height (Lam [y].e1) - 1 + height e'" by simp
next
case (App e1 e2)
hence ih1: "height (e1[x::=e']) \ ((height e1) - 1) + (height e')"
and ih2: "height (e2[x::=e']) \ ((height e2) - 1) + (height e')" by simp_all
then show "height ((App e1 e2)[x::=e']) \ height (App e1 e2) - 1 + height e'" by simp
qed
end
¤ Dauer der Verarbeitung: 0.1 Sekunden
(vorverarbeitet)
¤
|
Haftungshinweis
Die Informationen auf dieser Webseite wurden
nach bestem Wissen sorgfältig zusammengestellt. Es wird jedoch weder Vollständigkeit, noch Richtigkeit,
noch Qualität der bereit gestellten Informationen zugesichert.
Bemerkung:
Die farbliche Syntaxdarstellung ist noch experimentell.
|